Treatment of Chronic Hepatitis D Patients with Pegylated Interferon: A Real-World Experience. Issue 5 (July 2014) - Abbas, Zaigham; Memon, Mohammad S; Mithani, Hammad; Jafri, Wasim; Hamid, Saeed
Background: Published experience of treating chronic hepatitis D patients with pegylated interferon (PEG-IFN)-α is limited. The aim of this study was to determine the efficacy of 48 weeks of treatment with PEG-IFN in naive patients outside the clinical trial setting, in the real world. Methods: Patients with chronic hepatitis D were treated with PEG-IFN. The primary end points were sustained clearance of HDV RNA and normal alanine aminotransferase (ALT) at 24 weeks post-treatment. Results: The total number of patients treated with PEG-IFN was 104; 91 males, mean age ±sd 30.1 ±10.0 years (range 15–55). Cirrhosis was present in 41 patients. With an intention-to-treat analysis, end of treatment virological response (ETR) was achieved in 44 (42.3%), normalization of ALT in 38 (35%) and a combined response in 23 (22.1%) patients. Sustained virological response (SVR) at 24 weeks post-treatment was seen in 24 (23.1%) patients each for the virological and bio-chemical responses and in 13 (12.5%) as combined response. Both ETR and SVR were associated with a negative HDV RNA at 24 weeks of treatment ( P =0.001 and P =0.000, respectively). Detectable HDV RNA at this point had a positive predictive value of 0.95 (range 0.85–0.99) for detectable RNA at 6 months post-treatment. End of treatment biological response, that is, normal ALT at the end of treatment was also a predictor of ETR and SVR ( P =0.004 and P =0.041, respectively). Conclusions: Treatment with PEG-IFN for hepatitis D is of limited efficacy. Detectable HDV RNA at 24 weeks of treatment is a predictor for a failed SVR.